Alkaline Reflux Esophageal Stenosis After Total Gastrectomy - Carriquiry, Luis A.; Luksenburg, Jaime (Cirugía del Uruguay, 1982)
The authors present one case of Esophagostenosis due to alkaline re flux after total gastrectomy. The patient was successfully treated with antireflux surgery. The importance of this entity is emphasized, due to the presently more widesPread use of total gastrectomy. The pathogenic role of the jejunumesophageal reflux is analized on the basis of clinical and experimental considerations: emphasizing the deleterious effect of gall and more gpecifically the nonconjugated biliary salts, in an alkaline or neutral pH environment.